(untitled) (Minerva. Revista de Filología Clásica, 2019)
Reseña de Monica H. Green, Making Women’s Medicine Masculine . The Rise of Male Authority in Pre-Modern Gynaecology, Oxford University Press, 2008, 409 pp. ISBN 978-0-19-921149-4